Analysis of Gender Issues in Tafsir al-Misbah by M. Quraish Shihab and Turjumān al-Mustafīd by Abd Ra'uf Singkel by Muqāran Method - Muhsin Mahfudz; Abdullah Azzam Bishri; Lukman (Pappaseng: International Journal of Islamic Literacy and Society, 2022)
This paper examines one application of the muqaran technique in Saifuddin and Wardani's readings of the archipelago. This approach compares interpretations and commentators. This research is of the literature review variety. While the employed methodologies and approaches are the muqaran (comparison) method and the interpretation approach. This article indicates that the muqaran approach comprises comparisons of verses with verses containing comparable editorials, comparisons of verses with hadiths that are suggested to be contradictory, and comparisons of mufassir leaders' viewpoints. On the other hand, the comparison method's components depend on the comparison pattern employed. The area of opinion comparison between mufassir figures is expansive. Similarities and differences exist between the comparative technique and the methods employed or utilized in the text. However, the verse grouping and mapping of mufassir viewpoints are distinct.